Clinical and economic analysis of the prescription of drugs for postoperative support of total hip arthroplasty - E.V. Brodska; O.V. Makarenko; S.M. Dronov (Medičnì Perspektivi, 2025)
A well-founded choice of means of medical support for patients after total hip arthroplasty and rational use of financial resources for this purpose allow to achieve the maximum possible socio-economic effect in the future. Its methodological basis is made up of clinical and economic concepts based on the concepts of cost (price, expenses) and clinical effectiveness of the intervention (treatment results). The aim of the study was to determine the financial component of medical support in the postoperative period of total hip arthroplasty using ABC/VEN analysis (Vital Essential Non-essential). In the current study, the ranking of medical products when conducting both ABC/VEN analysis was carried out by the number of prescriptions. The number of prescriptions is a more indicative approach, as it demonstrates the real frequency of drug use in practice, the relevance and demand for specific medications in real-world conditions, allowing for a more accurate determination of priority drugs for clinical use and, accordingly, providing a more relevant and practical assessment of drug needs. The number of observations (n), minimum and maximum values (min – max) were used to describe the variables, quantitative data were presented as the arithmetic mean and standard deviation. Qualitative data - in the format n (%). Results - analysis of prescriptions from medical records of patients with dysplastic coxarthrosis revealed that 6548 prescriptions were made for 367 people during the study period. The results of the integrated ABC/VEN analysis showed that in the context of the most costly group “A”, the main financial resources were spent on providing long-term antithrombotic therapy to prevent pulmonary embolism and lower limb vein thrombosis, the total amount for 2754 prescriptions (42.1% of all prescriptions) was 1,745,478.90 UAH. Less costly (group “B”, 2351 prescriptions) were drugs prescribed for antibiotic prophylaxis of infectious complications. In general, the costs of drugs in group “B” (35.9% of all prescriptions) amounted to 552,820.30 UAH, which corresponded to 21.6% of the financial costs for medical support of patients after TEP. The least expensive group "C" consisted mostly of secondary category N means, which accounted for 17.9% (1173 out of 6548) of the total number of prescriptions and accounted for 6.7% (171,986.75 out of 2,559,353.23 UAH) of the total amount of expenses. «Vital» category V means in this analysis group accounted for 4.1% (270 out of 6548) of all prescriptions, and the expenses for them were 3.5% (89,067.28 out of 2,559,353.23 UAH). The share of financial expenses for these means amounted to half (52.8%) of the total budget for medical support of patients after total hip arthroplasty, which in monetary equivalent was 1,350,380.53 UAH. The leading positions in terms of costs were occupied by vital category V drugs – the synthetic selective inhibitor of activated factor X fondaparinux (“Arixtra”) and the competitive reversible direct thrombin inhibitor dabigatran etexilate (“Pradaxa”), the share of prescriptions of which was 89.4% and 82.3%, respectively.